Impact of Economic Growth, Environmental Pollution, and Energy Consumption on Health Expenditure and R&D Expenditure of ASEAN Countries - Muhammad Haseeb; Sebastian Kot; Hafezali Iqbal Hussain; Kittisak Jermsittiparsert (Energies, 2019)
The purpose of the current study was to examine the determinants of R&D expenditure and health expenditure of ASEAN countries. The research objectives were developed to analyze the short-term as well as the long-term impact of economic growth, environmental pollution, and energy consumption on health and R&D expenditures. The data was collected for ten years for ASEAN countries using the Auto-Regressive Distributed Lag (ARDL) approach, which helped the researcher to assess long-run as well as the short-run association of these variables. The findings revealed that environmental pollution, energy consumption, and economic growth had a significant positive impact on health expenditure as well as on R&D expenditure of ASEAN countries in long-run. The findings further revealed that environmental pollution and economic growth had a significant impact on R&D expenditure in short-run; however, there was no significant impact of energy consumption on R&D expenditure in short-run. It was also found that there was no significant impact of any of the independent variables, i.e., energy consumption, economic growth, and environmental pollution, on health expenditure in short-run. The current study and findings have significant implications in theory and practice.